ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENYERAPAN ANGGARAN DANA DESA - MANJALENI, ROLA (Jurnal Akuntansi dan Bisnis, 2025)
This study was conducted with the aim of identifying various factors that influence the realization of the village fund budget in the Tarogong Kidul District Government, Garut Regency, West Java. The research subjects included all employees within the Tarogong Kidul District Government, totaling 99 people, with the sample determined through a purposive sampling method. Primary data became the main data source collected through a questionnaire instrument. A quantitative approach with multiple linear regression analysis techniques was applied in this study. The research variables are divided into independent and dependent variables. The independent variables include the quality of human resources (X1), budget planning (X2), and procurement of goods and services (X3). The research findings show that the quality of human resources, budget planning, and procurement of goods and services have a significant influence on the realization of the village fund budget.